Investigating Membrane Protection of Red Blood Cells in the Presence of Mono and Disaccharides at Hypothermic Storage Conditions - Hickman, Josie Annette (East Carolina University)
The maximum approved storage time of red blood cells under hypothermic conditions is 42 days when treated with an appropriate additive solution. Here, we investigated the possible protective properties of various mono and disaccharides when incubated with red blood cells. Absorbance measurements were used to monitor the amount of hemoglobin found in the supernatant as samples were incubated. A decrease in hemolysis was observed in the red blood cells when incubated with each of the sugar molecules. A decrease in hemolysis due to the addition of the sugar suggests that they are acting as osmolytes and influencing the properties of the red cell's hydration via preferential interactions. Osmotic fragility experiments were also conducted to assess if membrane flexibility was being compromised due to the addition of sugar during incubation by quantifying the percent hemolysis at various salt concentrations. This was not the case among any of the sugars, further suggesting that there may be membrane protection in the presence of each mono and disaccharide. Due to sucrose having the slowest rate of hemolysis but not being able to be used in a clinical setting, sucralose was of particular interest due to structural similarities. A calcein leakage assay was utilized to see if the sugar molecule is able to offer the same protection in the absence of proteins within the membrane. This assay was conducted on model phospholipid membrane 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), where liposomes encapsulating the fluorescent dyecalcein were incubated with sucralose post liposome formation. The fluorescence intensity measured for each sample was used to calculate the selfquenching efficiency of the dye which provides information about membrane permeation. The data revealed that self-quenching efficiency decreased as the concentration of sucralose increased indicating that the integrity of model membranes was not maintained during hypothermic storage in the same manner as the red cell membranes.
Keywords: Erythrocytes; Hemolysis and hemolysins